Tendencias en la matrícula de educación superior : Argentina, Brasil, Chile, Colombia, Paraguay y Uruguay : 2000-2018 - Álvarez, María Franci Sussan (2022)
Fil: Fantin, María Alejandra. Universidad Nacional Villa María; Argentina..